Characterization of stromal vascular fraction and adipose stem cells from subcutaneous, preperitoneal and visceral morbidly obese human adipose tissue depots. - Karina Ribeiro Silva; Isis Côrtes; Sally Liechocki; João Regis Ivar Carneiro; Antônio Augusto Peixoto Souza; Radovan Borojevic; Clarissa Menezes Maya-Monteiro; Leandra Santos Baptista (PLoS ONE, 2017)
BACKGROUND/OBJECTIVES:The pathological condition of obesity is accompanied by a dysfunctional adipose tissue. We postulate that subcutaneous, preperitoneal and visceral obese abdominal white adipose tissue depots could have stromal vascular fractions (SVF) with distinct composition and adipose stem cells (ASC) that would differentially account for the pathogenesis of obesity. METHODS:In order to evaluate the distribution of SVF subpopulations, samples of subcutaneous, preperitoneal and visceral adipose tissues from morbidly obese women (n = 12, BMI: 46.2±5.1 kg/m2) were collected during bariatric surgery, enzymatically digested and analyzed by flow cytometry (n = 12). ASC from all depots were evaluated for morphology, surface expression, ability to accumulate lipid after induction and cytokine secretion (n = 3). RESULTS:A high content of preadipocytes was found in the SVF of subcutaneous depot (p = 0.0178). ASC from the three depots had similar fibroblastoid morphology with a homogeneous expression of CD34, CD146, CD105, CD73 and CD90. ASC from the visceral depot secreted the highest levels of IL-6, MCP-1 and G-CSF (p = 0.0278). Interestingly, preperitoneal ASC under lipid accumulation stimulus showed the lowest levels of all the secreted cytokines, except for adiponectin that was enhanced (p = 0.0278). CONCLUSIONS:ASC from preperitoneal adipose tissue revealed the less pro-inflammatory properties, although it is an internal adipose depot. Conversely, ASC from visceral adipose tissue are the most pro-inflammatory. Therefore, ASC from subcutaneous, visceral and preperitoneal adipose depots could differentially contribute to the chronic inflammatory scenario of obesity.